A study of menstrual pattern and prevalence of dysmenorrhea during menstruation among school going adolescent girls in Lucknow district, Uttar Pradesh, India - Sinha, Shivani; Srivastava, Jyoti Prakash; Sachan, Beena; Singh, Raj Bahadur (International Journal Of Community Medicine And Public Health, 2017)
Background: The world health organization (WHO) has defined adolescence as the age group of 10-19 years. One of the major physiological changes that take place in adolescent girls is the onset of menarche, which is often associated with problems of irregular menstruation, excessive bleeding, and dysmenorrhea. Objective of the study is to study the menstrual pattern and the prevalence of dysmenorrhoea among school going adolescent girls in Lucknow district of Uttar Pradesh, India. Methods: It was a school based cross-sectional study carried out in Lucknow district from October 2013 to September 2014. A total of 640 adolescent girls were included in the study. Data was collected, compiled and tabulated using Microsoft Excel and analysed using SPSS 17.0 version for calculation of percentages. Results: The overall prevalence of dysmenorrhoea was found to be 73.9% with 74.4% girls in urban schools and 72.7% girls in rural schools. Conclusions: The mean age at menarche was 12.87 years (S.D±1.45). In urban area it was 12.69 years (S.D±1.37) and 13.22 years (S.D±1.56) in rural areas. There is a need of health education for adolescents. Menstruation is an important milestone for adolescent girls and menstrual problems are common among adolescent girls.Education regarding menstrual.